Rational blinders: strategic selection of risk models and bank capital regulation - Jean-Edouard Colliard (European Central Bank (ECB), 2014)
The regulatory use of banks' internal models aims at making capital requirements more accurate and reducing regulatory arbitrage, but may also give banks incentives to choose their risk models strategically. Current policy answers to this problem include the use of risk-weight floors and leverage ratios. I show that banks for which those are binding reduce their credit supply, which drives interest rates up, invites other banks to adopt optimistic models and possibly increases aggregate risk in the banking sector. Instead, the strategic use of risk models can be avoided by imposing penalties on banks with low risk-weights when they suffer abnormal losses or bailing out defaulting banks that truthfully reported high risk measures. If such selective bail-outs are not desirable, second-best capital requirements still rely on internal models, but less than in the first-best.
Keywords: D82; D84; G21; G32; G38; 330; Basel risk-weights; internal risk models; leverage ratio; tail risk